STRUKTUR DAN POLA KEPEMIMPINAN KYAI DALAM PESANTREN DI JAWA - Amir Fadhilah (State Institute of Islamic Studies (IAIN) Palu, 2011)
Abstract: The world of pesantren and the Islamic clerics’ charisma is one of the interesting phenomena to be studied. The style of clerics’ life and religious students is so great that it makes Islamic boarding school posess a multi-dimensional function: The Kyais not only are not only required as priests in religious ceremonies and rituals , but also often required her presence to resolve the case or the difficulties that befall the community. In this context, the role of the Islamic clerics is increasingly rooted in the community when their presences are believed to bring fortune. The existence of structures and patterns of authority (leadership) clerics in the Islamic world remain sustainable, because the Islamic clerics have internal social nets (among the religious schools) and external social netwoeks (with the world outside pesantren), includes genealogical network, ideological network, intellectual network, theological network, and spiritual network.Kata Kunci: pola kepemimpinan kyai, pesantren, kharismatik dan jaringan